CULTURAL EDUCATION AS A SOLUTION TO IDENTITY CRISIS: DEVELOPMENT AND IMPLEMENTATION OF JARAN BODHAG-BASED LEARNING MODULES - Rizqi Nur Salia; Mudafiatun Isriyah; Weni Kurnia Rahmawati (CV. TOTUS TUUS, 2025)
Identity confusion among university-age students is linked to anxiety, motivational decline, and reduced academic responsibility. In pesantren contexts, mahasantri must reconcile academic rigor with spiritual–communal norms, making culturally grounded interventions necessary. Objective: To develop and validate a counselor-ready module that uses the East Javanese folk performance Jaran Bodhag to strengthen identity clarification (discipline, resilience, simplicity, responsibility) among mahasantri at PPA Ibnu Katsir Putri, Jember. Methods: A Research & Development design following ADDIE guided needs analysis, co-design, expert content validation (CVI/Aiken’s V framework), prototype refinement, and a small-scale field tryout. Participants were 25 female mahasantri selected purposively. Data sources included expert ratings, fidelity checklists, learner acceptability questionnaires, and brief reflections. Results: Expert appraisal yielded an overall validity score of 80%, classifying the product as “valid/feasible with minor revision.” The tryout showed high acceptability and contextual fit; fidelity logs indicated deliverability within regular guidance sessions. Priority revisions were to (a) sharpen the service-plan sequencing and (b) add a concise glossary. Conclusion: A culturally grounded, arts-integrated module is feasible and acceptable for addressing identity-crisis indicators among mahasantri and is ready for broader piloting. Usefulness: The product offers a practical, counselor-facing package aligned with school guidance routines, enhancing cultural resonance and implementation fidelity. Suggestions: Future studies should employ multi-expert CVI/CR procedures, report item-level indices, use validated pre–post measures with comparator groups, document implementation fidelity systematically, and examine mediators (e.g., self-efficacy) across diverse pesantren settings.